Maternal nutritional status and pregnancy symptoms among healthy pregnant and gestational diabetic women - Liang, Teow Ying (2012)
The aims of this study were to compare and correlate maternal nutritional status and pregnancy symptoms between healthy pregnant and gestational diabetic women. A total of I 08 pregnant women (77 healthy and 31 gestational diabetic), aged between 19 to 34 year-old, within the gestational age of 32 to 40 weeks were recruited from Obstetric and Gynecology, Hospital Universiti Sains Malaysia. Pregnancy symptoms score were assessed with validated Pregnancy Symptoms Questionnaire. Independent t-test, Mann-Whitney test, Pearson and Spearman correlations were used for statistical analysis. Gestational diabetic women had significantly higher pre-pregnancy body mass index (p=0.026), body fat mass at late trimester (p=O.OOI), experienced lower frequency (p=0.044) and higher severity (p=0.026) of headache than healthy pregnant women. Maternal weight gain rate was correlated positively with various pregnancy symptoms among pregnant women. There is a significant difference on maternal nutritional status and general pregnancy symptoms between healthy pregnant and gestational diabetic women. There is also a significant correlation of maternal weight gain rate and pregnancy symptoms among all pregnant women.